Bonhoeffer's ethically oriented self: responsible 'as a human being' - Elliston, C; Clark Elliston (2012)
Dietrich Bonhoeffer offers a vibrant, theological depiction of the self constituted by and for the other in responsibility. The thesis argues that the concept of orientation is crucial for understanding this self; the self is a being oriented to, or away from, the other. To grasp the distinctiveness of Bonhoeffer’s self this thesis aims to open up critical conversation with his historical contemporaries, Emmanuel Levinas and Simone Weil. Like Levinas, Bonhoeffer depicts the self as confronted by the other. Yet unlike Levinas, Bonhoeffer’s other does not render the self a ‘host-hostage’. An oriented self, grounded in Bonhoeffer’s theology, is neither dominating nor other-dominated. Bringing Bonhoeffer and Weil into critical dialogue with one another helps to describe the precise way in which the self is responsible for the other. Conversation with Weil refines Bonhoeffer’s account of responsibility by integrating her account of attention into his account of existing on behalf of another. It is also neither self-affirming nor self-negating. The first chapter outlines two recent conceptions of the self as oriented; but each, as will be demonstrated, does not recognise fully the ethical contours of the oriented self. The second chapter examines in detail Bonhoeffer’s contributions to a Christological account of the responsibly oriented self. Integral to this account are the images of ‘the heart turned in on itself’ (cor curvum in se) and Christ who is fundamentally ‘for’ the other. The third chapter converses with Emmanuel Levinas, both constructively and critically. Of help is Levinas’s reading of the other as a confrontation to the self. His rendering of the other as dominating, or holding hostage, the self is a serious issue. Such a construction resists positive elements of the self-other relation. The fourth chapter investigates what conversation with Simone Weil can offer to Bonhoeffer’s framework. Her concept of attention helps to articulate how the self becomes a self through engagement with another. The fifth chapter presents Adolph Eichmann, as portrayed by Hannah Arendt, as the supreme and pivotal opposite of attentive responsibility. In Eichmann’s irresponsibility and disunity [while doing his ‘duties’] one finds justification for a fundamental re-working of ethics in a Bonhoefferian vein. The image of the ethically blind cor curvum in se exposes Eichmann’s fundamental issue. In contrast, Bonhoeffer’s ethically oriented self both perceives the other and gives of itself as for that other.